Implementasi Management By Objective (MBO) Dalam Bidang Sdm Pada Perusahaan Otomotif Di Karawang - Dita Sukma Palupi; Uus Mohammad Darul Fadli (CV. ITTC INDONESIA, 2024)
Management By Objective (MBO) to improve employee performance and employee career growth in achieving the company's objectives, assessment of the entire employee's performance in a company with objective assessment by employees in the automotive company in the caravan itself using the MBO. The aim is to understand the performance assessment with the management by objective (MBO) in the Automotive Company in Karawang and understand the effectiveness of work by using the method of MBO in the automobile enterprise at Karawang the process of determining the human resource needs, which means meeting those needs with the needs of the organization so that its implementation is integrated with the organization's plan. The method is conducted with interviews, surveys, and observations to employees of the automotive company in Karawang. The data collected is using modified questionnaires and verified interviews conducted to 6 employees. The results and interpretation are good because more than 80% of MBOs are effective for the company based on employee interviews already conducted at the automotive company in Karawang.